A pilot multi‐centre prospective randomised controlled trial of RECELL for the treatment of venous leg ulcers. Issue 3 (26th February 2020) - Hayes, Paul D.; Harding, Keith G.; Johnson, Susan M.; McCollum, Charles; Téot, Luc; Mercer, Kevin; Russell, David
Abstract: Venous leg ulcers (VLUs) have a significant impact on approximately 3% of the adult population worldwide, with a mean NHS wound care cost of £7600 per VLU over 12 months. The standard care for VLUs is compression therapy, with a significant number of ulcers failing to heal with this treatment, especially with wound size being a risk factor for non‐healing. This multicentre, prospective, randomised trial evaluated the safety and effectiveness of autologous skin cell suspension (ASCS) combined with compression therapy compared with standard compression alone (Control) for the treatment of VLUs. Incidence of complete wound closure at 14 weeks, donor site closure, pain, Health‐Related Quality of Life (HRQoL), satisfaction, and safety were assessed in 52 patients. At Week 14, VLUs treated with ASCS + compression had a statistically greater decrease in ulcer area compared with the Control (8.94 cm 2 versus 1.23 cm 2, P = .0143). This finding was largely driven by ulcers >10 to 80 cm 2 in size, as these ulcers had a higher mean percentage of reepithelialization at 14 weeks (ASCS + compression: 69.97% and Control: 11.07%, P = .0480). Additionally, subjects treated with ASCS + compression experienced a decrease in pain and an increase in HRQoL compared with the Control. This study indicates that application of ASCS + compression accelerates healing in large venous ulcers.